Implementasi Model Pembelajaran Contextual Teaching and Learning dalam Pembelajaran Bahasa Arab di Madrasah Tsanawiyah Negeri - Anggita; Ubadah; Atna Akhiryani (Albariq: Jurnal Pendidikan Bahasa Arab, 2023)
This research highlights the challenges in Arabic language learning at Madrasah Tsanawiyah Negeri 3 Palu City, especially the lack of learner involvement and their difficulty in linking learning materials with daily life. To overcome these problems, the implementation of Contextual Teaching and Learning model is expected to build learners' engagement, to connect learning materials with real contexts, and to motivate learners in developing Arabic language skills. This research uses a qualitative method which aims to find out how the implementation of Contextual Teaching and Learning learning model in Arabic language learning and what are the inhibiting and supporting factors for the implementation of Contextual Teaching and Learning learning model in Arabic language learning which focuses on class VIII A at Madrasah Tsanawiyah Negeri 3 Palu City. Data were collected through interviews, observations, and documentation. The results showed that the implementation of the learning model had a positive impact with several supporting factors such as good relationships between teachers and students, high teacher interest in interactive learning, and active participation of students. However, constraints such as the lack of facilities and technology, as well as the disparity of learners' Arabic language ability, also affect the learning process.